Pengaruh Kecerdasan Emosional terhadap Hasil Belajar Matematika Siswa Kelas 5 di SDN Kubang Sepat 1 Kota Cilegon - Fauziyah, Siti; Tiurlina, Tiurlina; Alfarisa, Fitri (Didaktika, 2022)
Emotional intelligence is the ability to manage emotions towards oneself when faced with any conditions so that they can make decisions that are beneficial for themselves. Mathematics is one of the subjects that contains symbols, numbers that have a certain meaning. Based on the results of observations at SDN Kubang Sepat 1 Cilegon, it was found that in learning mathematics, many students were indifferent, students gave up easily and did not have enthusiasm in learning mathematics. Most of them lack the confidence to learn mathematics and do not like to study mathematics on the grounds that learning mathematics is difficult to understand and many experience problems in solving math problems. All attitudes shown by students are centered on the emotions that exist within them. The purpose of this study was to determine the effect of emotional intelligence on learning achievement in mathematics. The research method used is Ex-postfacto quantitative approach. The research instrument used was a measurement scale of emotional intelligence and a test of mathematics learning outcomes. The research results obtained include (1) students' emotional intelligence is divided into three categories, namely low 0 students, medium 29 students and high 3 students (2) students' mathematics learning outcomes are divided into three categories, namely low 5 students, medium 20 students and high 7 students (3) There is an influence between emotional intelligence on mathematics learning outcomes seen from the significance test value of 0.000 (4) The magnitude of the influence of emotional intelligence on student learning outcomes is 34,7%. The conclusions obtained from the results of this study are the influence of emotional intelligence on the mathematics learning outcomes of students at SDN Kubang Sepat 1 Cilegon.